Banggai cardinalfish and its microhabitats in a warming world: a preliminary study. (April 2019) - Moore, A M; Ndobe, S; Yasir, I; Ambo-Rappe, R; Jompa, J
Abstract: Global changes in the Anthropocene are affecting marine ecosystems in many ways, including alterations in long-established inter-species relationships. The Banggai cardinalfish Pterapogon kauderni, a species of global conservation concern, is highly dependent on benthic organisms serving as microhabitat. The objective of this study was to evaluate the effects of global change, in particular rising sea temperature, on P . kauderni and three key associated microhabitats: hard corals (Scleractinia), sea urchins (Diadematidae), and sea anemones (Actinia). Data collected before, during, and after the 2016 global coral bleaching event from P . kauderni habitat in the Banggai Archipelago, including coral bleaching (by genus) and P . kauderni (by life stage) microhabitat association (species or genus, coral life-form), were complemented by a literature review. While coral bleaching and mortality was less severe than in many other regions, hard coral genera and life-forms preferred by P . kauderni were disproportionately affected, and P . kauderni hosting sea anemones also bleached. Coral, sea urchin and sea anemone reproduction, larval development, and recruitment may be negatively affected. Likely post-settlement effects on sea urchin and sea anemone growth and survival are unclear. Direct impacts on P . kauderni are likely, including metabolic rate change with consequences for growth and longevity. Indirect impacts (e.g. changes in plankton composition and abundance, increased storm frequency/severity) will affect P . kauderni and all its microhabitats. This evaluation for P . kauderni, its key microhabitat groups, and their association, points towards increased need for both conservation action and research to fill identified knowledge gaps.